Anthropometry as Indicator of the Family Economic Condition - Wahyuniar, Lely; Sutrisna, Bambang; Djauhari, Abas B.; Djuwita, Ratna (Media Kesehatan Masyarakat Indonesia, 2020)
The prevalence of Indonesian population experiencing hunger reaches 20.1%. Anthropometry is considered capable to measure socio-economic conditions because it is directly related to the financial purchasing power of food that affects intake patterns. The aim of this study is to test the reliability of the family anthropometry using Height for Age Z Score (HAZ) index and Body Mass Index Z Score (BMIZ) as indicator of the family economic condition. This cross-sectional study design located in Astanajapura (Rural) and Kesambi (Urban) Subdistrict, Cirebon, West Java. The stratification sampling method was held to obtain samples from all main family members of the selected households (1,999 persons) from 405 families. Data analysis used ROC method to obtain the cut-off points of anthropometry index, validity test for sensitivity and specificity, and Kappa test for the reliability test. The findings indicate that the family HAZ anthropometry index could represent the family economic condition better than the BMIZ and it is reliable to become an indicator for the economic condition both in rural and urban areas. There is a positive correlation between consumption per capita and the HAZ index where the higher the family HAZ z score is, the higher the family consumption per capita. The method can be used to measure the poor prevalence in macro level and select the target of poor families in the micro level using the family HAZ anthropometry index. It is recommended to use HAZ index to estimate prevalence of poor families within the micro level, but the process must not include children under two years old due to the technical obstacle during measurement and other substance factors. Further research is needed to produce a more accurate method in using the family anthropometry as an indicator of family economic condition.